Mature Cystic Teratoma of Liver - Gupta, Richa (EL-MED-Pub, 2013)
A four-year-old boy presented with constipation and mild abdominal distention for one year. Radiologic investigations showed a multiloculated cystic lesion in the caudate lobe of liver with focal calcification in the wall. The child underwent laparotomy with marsupialization of the cystic lesion. Histopathologic examination showed mature teratoma of liver.